DIGITAL TRANSFORMATION IN THE COURSE FOR DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS - Rafael Lisinus Ginting; Elizon Nainggolan; Albert Pauli Sirait; Ishaq Matondang; Mirza Irawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to digitize learning tools for the Guidance of Children with Special Needs courses in the Guidance and Counseling study program, digitize the lecture process for the Guidance of Children with Special Needs courses at the Guidance and Counseling study program, transform the courses for the Development of Children with Special Needs digitally in the Guidance and Counseling study program and test the effectiveness of digital transformation of the Guidance for Children with Special Needs courses .The digital transformation is carried out using the R&D method. The development model used in this study is a 3D model: the definition stage (Define), the design stage (Design), the development stage (Develop) which is carried out in the Guidance and Counseling study program. In realizing the digital transformation of the Fostering Children with Special Needs course, several experts are involved, including learning design experts, IT experts and material experts.The results of this study are expected to be the beginning of positive developments for the use of IT in learning. This research is also expected to be input for lecturers who want to transform their lectures digitally so that digital transformation will appear in other courses at Medan State University..